Evaluating the quality of educational services based on student\'s viewpoint according to SERVQUAL model in the Faculty of Mathematical, Statistical and Computer Sciences at Tehran University - Hasan Misaii; Mojgan Mohammadimehr (Journal of Medical Education and Development, 2018)
Introduction: Evaluating the quality of educational services is one of the most important jobs of the higher education. The SERVQUAL model for gap analysis evaluates the quality of services based on customer’s viewpoint. A good plan for increasing educational services quality can be achieved by SERVQUAL model. This study aims to evaluate the quality of educational services at Faculty of Mathematical, Statistics and Computer Sciences of Tehran University based on SERVQUAL model.